Enhancement of aromatic hydrocarbon production and suppression of coke formation in catalytic pyrolysis of biomass / Pouya Sirous Rezaei - Pouya Sirous, Rezaei (2016)

(untitled)
The concern for depletion of fossil fuels and their growing environmental threats necessitates to develop efficient techniques for utilization of lignocellulosic biomass as an alternative fuel source which is renewable and environmentally safe. Pyrolysis is an economically feasible process for large-scale exploitation of biomass. However, bio-oil which is the liquid product of biomass pyrolysis has high oxygen content, and needs to be deoxygenated to hydrocarbons in order to be used as fuel additive. Catalytic pyrolysis using zeolites as catalyst is considered as an efficient technology since it includes both steps of pyrolysis and catalytic upgrading in one unit. Among the three major lignocellulosic components (cellulose, hemicellulose and lignin), lignin is the most difficult fraction of biomass to be deoxygenated. In catalytic conversion of methanol co-fed with m-cresol or phenol as lignin model compounds over HBeta catalyst in a fixed-bed reactor, it was revealed that co-feeding phenol or m-cresol with methanol causes significant deactivation of HBeta and remarkable reduction in aromatic hydrocarbons yield due to strong adsorption of phenolics on zeolite acid sites. Hence, pure zeolites are not appropriate catalysts for upgrading of the lignocellulosic biomass with high content of lignin. In this research, bifunctional Fe/HBeta catalyst showed to be efficient for production of aromatic hydrocarbons in catalytic pyrolysis of palm kernel shell waste with high lignin content of about 50 wt%. Lignin derived phenolics were deoxygenated through hydrogenolysis reaction promoted by Fe active sites. The adsorption of phenol on zeolite was shown to be highly affected by reaction temperature and catalyst properties such as pore size, crystallite size and strength distribution of zeolite acid sites. One main challenge in atmospheric upgrading of biomass derived feedstocks over zeolites is high formation and deposition of coke which results in rapid catalyst deactivation. Meanwhile, coke formation is a competing reaction with production of valuable compounds like aromatic hydrocarbons. Coke is one major undesired product of this process which its iv high yield is due to low hydrogen to carbon effective ratio of biomass and in turn low hydrogen content in hydrocarbon pool inside catalyst. In this study, catalytic pyrolysis of cellulose as biomass model compound was conducted using HZSM-5 (Si/Al: 30), HY (Si/Al: 30) and physically mixed catalysts of HZSM-5 (Si/Al: 30) and dealuminated HY (Si/Al: 327) in order to investigate the dependency of formation of both types of thermal and catalytic coke on zeolite characteristics. Coke formation over physically mixed catalysts of HZSM-5 and dealuminated HY was remarkably lower than that over HZSM-5 and HY. The aromatic hydrocarbons yield was also considerably enhanced over the physically mixed catalysts compared to HZSM-5 and HY. It was shown that there is a significant interaction between zeolite pore structure and density of acid sites which could be taken into account for designing more efficient catalysts to achieve lower coke formation and higher production of desired products. The catalysts used in this study were characterized by XRF, XRD, N2 adsorption, NH3-TPD, H2-TPR, FTIR and TGA, and liquid products were analyzed by GC/MS.